Desarrollo De Pasantía En La Empresa Chaneme Comercial S.A. - Infraestructura (2025)
This document describes the activities and responsibilities carried out during the internship period at the company Chaneme Comercial S.A. Infraestructura, dedicated to the marketing of yellow machinery and spare parts from the VOLVO and SDLG brands, in the area of supply chain are presented, applying the knowledge and skills acquired during the academic training in the International Trade career at the Antonio Nariño University, thus detailing the functions performed by the intern.